MOTIVASI YANG MEMPENGARUHI MAHASISWA PARIWISATA DAN PERHOTELAN DI BALI UNTUK BELAJAR BAHASA INGGRIS - I Wayan Suadnyana; Dika Pranadwipa Koeswiryono (Universitas Triatma Mulya, 2023)
This research aims to investigate the motivation of students majoring in tourism and hospitality in Bali in learning English. The decision to explore this topic was driven by the importance of English in Bali's rapidly growing tourism industry and the challenges faced by students in developing their English language skills. The research method used in this study is a quantitative approach using a questionnaire as a data collection instrument. Respondents are students majoring in tourism and hospitality at IPB International, Bali. Data were analyzed using IBM SPSS Statistics Version 25 software to measure their intrinsic and extrinsic motivation in learning English. The results showed that extrinsic motivation, such as the hope of getting a good job, had a stronger influence (mean score 35.38) compared to intrinsic motivation (mean score 34.50), such as the desire to improve English language skills. Extrinsic factors, such as support from parents and lecturers in learning English, are also considered significant in motivating students.